2012
DOI: 10.1007/s10344-011-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of death of European Roe Deer before and after Eurasian Lynx reintroduction in the Bavarian Forest National Park

Abstract: The return of the Eurasian Lynx to Central Europe has led to a number of conflicts. A primary subject of discussion involves its predation on other wildlife species. Here, we investigated the influence of lynx on its main prey, Roe Deer, in the Bavarian Forest National Park in south-eastern Germany. We compared the survival rates of deer before and after reintroduction of lynx. The analysis is based on data from 1984 to 1988 and 2005 to 2008 of 88 and 99 radio-collared Roe Deer, respectively. During the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 45 publications
3
40
1
Order By: Relevance
“…In Grimsö, where lynx are present and the deer population has not been heavily managed, it is, perhaps, unsurprising that predictors related to lynx predation took on a central role. The 5–11% decrease in roe deer survival associated with lynx presence was similar to that observed after lynx re‐colonization of a site in Germany (∼10%; Heurich et al ). Populations of lynx and wolves are recovering in many parts of Europe and North America (Linnell et al , Mech and Boitani , Beschta and Ripple ).…”
Section: Discussionsupporting
confidence: 76%
“…In Grimsö, where lynx are present and the deer population has not been heavily managed, it is, perhaps, unsurprising that predictors related to lynx predation took on a central role. The 5–11% decrease in roe deer survival associated with lynx presence was similar to that observed after lynx re‐colonization of a site in Germany (∼10%; Heurich et al ). Populations of lynx and wolves are recovering in many parts of Europe and North America (Linnell et al , Mech and Boitani , Beschta and Ripple ).…”
Section: Discussionsupporting
confidence: 76%
“…2. Annual survival rates of roe deer in presence of both large predators and human hunters, only large predators or hunters, in absence of predation and human hunting in Southern Norway (present study), Bavarian Forest National Park in presence and absence of lynx (Heurich et al 2012), Tredozio (Focardi et al 2002), Storfosna (Cobben et al 2009), Chizé (Festa-Bianchet et al 2003 and Trois Fontaine (Gaillard et al 1993). The results from Trois Fontaine include only prime aged individuals.…”
Section: Discussionmentioning
confidence: 58%
“…The annual survival of adult roe deer was comparable, for example, to the values found for a population of black-tailed deer Odocoileus hemionus in Washington State (USA) (Bender et al 2004), subjected to both human harvest and natural predation (by the mountain lion Puma concolor L.). The only study conducted in Europe on roe deer mortality in presence of both human hunting and lynx predation (Heurich et al 2012) found that, after recolonisation of the study area by lynx, prime age roe deer survival was almost 20% lower than in absence of large predators (0.61 against 0.79).…”
Section: Discussionmentioning
confidence: 90%
“…Each location contains two or three traps. The box-trap (approved by the Swedish Environmental Protection Agency: registered as 'L6 Rådjursfälla M/Öster Malma') and similarly designed traps are widely used in research projects in countries that receive snow in the winter (Heurich et al 2012). Box-traps are constructed using Masonite boards for the side walls and door, while the roof and floor is composed of oil-tempered board and wooden bars (50 × 57 mm) in the short end front, opposite to the door (Supplementary 2).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, capturing wild animals causes stress and can potentially cause injuries, behavioural and physiological disorders and in some cases death (Arnemo et al 2006;Iossa et al 2007). To date several different methods have been used to capture different deer species such as drive nets (roe deer; Morellet et al 2009), net guns (whitetailed deer; Jacques et al 2009), remote drug delivery by darting (moose; Arnemo et al 2006), netted cage traps (white-tailed deer; VerCauteren et al 1999), drop-nets (mule deer;D'Eon et al 2003), cannon nets (Hawkins et al 1968), corrals (Rempel and Bertram 1975) and box-traps (roe deer; Heurich et al 2012). Several variables should be taken into consideration when decisions about which capture and handling methods are used, as some methods are not suitable in adverse weather conditions, in differing habitat types and population sizes.…”
mentioning
confidence: 99%